Cylindrical, periodic-surface-lattice cavity for a MM-wave Cherenkov source - MacLachlan, A; Konoplev, I; Robertson, C; Cross, A; Phelps, A (2012)
Using a cavity based on a periodic-surface-lattice (PSL) the concept of a high-power, 200GHz Cherenkov source is developed. If the PSL satisfies certain defined conditions single mode operation is observed. © 2012 IEEE.